Methionine at the Heart of Anabolism and Signaling: Perspectives From Budding Yeast - Walvekar, Adhish S.; Laxman, Sunil (Frontiers in Microbiology, 2019)
Studies using a fungal model, Saccharomyces cerevisiae, have been instrumental in advancing our understanding of sulfur metabolism in eukaryotes. Sulfur metabolites, particularly methionine and its derivatives, induce anabolic programs in yeast, and drive various processes integral to metabolism (one-carbon metabolism, nucleotide synthesis, and redox balance). Thereby, methionine also connects these processes with autophagy and epigenetic regulation. The direct involvement of methionine-derived metabolites in diverse chemistries such as transsulfuration and methylation reactions comes from the elegant positioning and safe handling of sulfur through these molecules. In this mini-review, we highlight studies from yeast that reveal how this amino acid holds a unique position in both metabolism and cell signaling, and illustrate cell fate decisions that methionine governs. We further discuss the interconnections between sulfur and NADPH metabolism, and highlight critical nodes around methionine metabolism that are promising for antifungal drug development.